Recent Advances in Polycaprolactones for Anticancer Drug Delivery - Abhi Bhadran; Tejas Shah; Godwin K. Babanyinah; Himanshu Polara; Somayeh Taslimy; Michael C. Biewer; Mihaela C. Stefan (MDPI AG, 2023)
Poly(ε-Caprolactone)s are biodegradable and biocompatible polyesters that have gained considerable attention for drug delivery applications due to their slow degradation and ease of functionalization. One of the significant advantages of polycaprolactone is its ability to attach various functionalities to its backbone, which is commonly accomplished through ring-opening polymerization (ROP) of functionalized caprolactone monomer. In this review, we aim to summarize some of the most recent advances in polycaprolactones and their potential application in drug delivery. We will discuss different types of polycaprolactone-based drug delivery systems and their behavior in response to different stimuli, their ability to target specific locations, morphology, as well as their drug loading and release capabilities.